Intersectoral value creation : a case study of developing cultural wellbeing services in the crossroads of cultural & social and health care sectors - Merkkiniemi, Heini (My University, 2021)
During the past two decades, interest towards cultural wellbeing has been growing in the level of policy, practice and research, providing a database of the benefits of using art for health and wellbeing. However, managers are challenged as bridgemakers of intersectoral collaborations and in implementing cultural wellbeing in local level operations. The target audience of this study includes future leaders, managers and entrepreneurs working as mediators, developers, facilitators, service providers and suppliers on cultural, social and health care sectors. The goal of this study is to support implementation of cultural value in social and health care sectors and create new knowledge on intersectoral value creation as managerial and entrepreneurial practices. The key questions are 1) what are the different perspectives and motives behind intersectoral collaborations, and 2) how cultural value is created and understood in different sectors. In conclusion, this thesis reflects upon the role of arts management in intersectoral value creation. The theoretical framework includes intersectoral collaboration and shared value creation as key concepts and describes the external and internal environment where intersectoral collaborations take place. It also highlights critical intersections ‘nodes’ within the networks and provides examples how cultural, societal and economical value of arts is realized in different sectors and understood in the level of policy, strategy and practice. The research approach is a qualitative case study, constructing an inductive research design. The data includes nine individual interviews conducted in 2017-2018 during a development project, Agency of Wellbeing, covering four different health care regions in Finland. The interviewees represent the perspectives of the professional network, including artists and cultural producers, executives and managers. In result, this study provides overviews on the overall condition of the ecosystem including benefits and challenges. The results show that although there is evidence and interest to support implementation of arts and culture in social and health care sectors in the individual and policy level, the value of arts is not fully realized and understood in the level of strategy and practise. Critical intersections and common ground were found within organisational and societal changes and managerial level collaborations, where implementation could proceed through intersectoral dialogue, co-creation and assessment of evaluative tools. Final discussions point out directions for further development within strategy, management and cultural entrepreneurship, in research and in practice.
Keywords: yhteistyö; hyvinvointi; yrittäjyys; kulttuuri; kehittäminen; fi=taidehallinto|sv=Arts Management|en=Arts Management|